TECTONIC-HYDROTHERMAL BRECCIATION ASSOCIATED WITH CALCITE PRECIPITATION AND PERMEABILITY DESTRUCTION IN MISSISSIPPIAN CARBONATE RESERVOIRS, MONTANA AND WYOMING - Katz D.A.; Eberli G.P.; Swart P.K.; Smith L.B. (My University, 2006)
The Mississippian Madison Formation contains abundant fracture zones and breccias that are hydrothermal in origin based on their morphology, distribution, and geochemical signature. The hydrothermal activity is related to crustal shortening during the Laramide orogeny. Brecciation is accompanied by dedolomitization, late-stage calcite precipitation, and porosity occlusion, especially in outcrop dolomites. The tectonic-hydrothermal late-stage calcite reduces permeability in outcrops and, potentially, high-quality subsurface reservoir rocks of the subsurface Madison Formation, Bighorn Basin. The reduction of permeability and porosity is increased along the margins of the Bighorn Basin but not predictable at outcrop scale. The destruction of porosity and permeability by hydrothermal activity in the Madison Formation is unique in comparison to studies that document enhanced porosity and permeability and invoke hydrothermal dolomitization models. Hydrothermal breccias from the Owl Creek thrust sheet are classified into four categories based on fracture density, calcite volume, and clast orientation. Shattered breccias dominate the leading edge of the tip of the Owl Creek thrust sheet in the eastern Owl Creek Mountains, where tectonic deformation is greatest, whereas fracture, mosaic, and chaotic breccias occur throughout the Bighorn Basin. The breccias are healed by calcite cements with δ18O values ranging between - 26.5 and - 15.1 ‰ Peedee belemnite (PDB), indicating that the cements were derived from isotopically depleted fluids with elevated temperatures. In the chaotic and mosaic breccia types, large rotated and angular clasts of the host rock float in the matrix of coarse and nonzoned late-stage calcite. This appearance, combined with similar δ18O values across even large calcite veins, indicates that the calcite precipitated rapidly after breciation. Values for δ13C (~5-12 ‰ PDB) from the frontal part of the Owl Creek thrust sheet indicate equilibrium between methane and CO2-bearing fluids at about 180°C. Fluid inclusions from the eastern basin margin show that these cements are in equilibrium with fluids having minimum temperatures between 120 and 140°C and formed from relatively low-salinity fluids, less than 5 wt.% NaCl. Strontium isotope ratios of these hydrothermal fluids are more radiogenic than proposed values for Mississippian seawater, suggesting that the fluids mixed with felsic-rich basement before migrating vertically into the Madison Formation. We envisage that the tectonic-hydrothermal late-stage calcite-cemented breccias and fractures originated from undersaturated meteoric groundwaters that migrated into the burial environment while dissolving and incorporating Ca2+ and CO32 and radiogenic Sr from the dissolution of the surrounding carbonates and the felsic basement, respectively. In the burial environment, these fluids were heated and mixed with hypersaline brines from deeply buried parts of the basement. Expulsion of these fluids along basement-rooted thrust faults into the overlying strata, including the Madison Formation, occurred most likely during shortening episodes of the Laramide orogeny by earthquake-induced rupturing of the host rock. The fluids were injected forcefully and in an explosive manner into the Madison Formation, causing brecciation and fracturing of the host rock, whereas the subsequent and sudden decrease in the partial pressure of CO2 caused the rapid precipitation of calcite cements. The explosive nature of hydrothermal fluid migration ultimately products heterogeneities in reservoir-quality carbonates. In general, flow units in Madison Formation are related to sequence boundaries, which create vertical subdivisions in the porous dolomite. The late-stage calcite cement surrounds hydrothermal breccia clasts and invades the dolomite, reducing porosity and permeability of the reservoir-quality rock. As a consequence, horizontal flow barriers and compartments are established that are locally unpredictable in their location and extent and regionally predictable along the margins of the Bighorn Basin. Copyright © 2006. The American Association of Petroleum Geologists. All rights reserved.